PlaSA Colombia - CGIAR (CGIAR Initiative on National Policies and Strategies, 2023)
PlaSA Colombia is a tool to understand the country’s food systems. It arises within the framework of the CGIAR initiative on National Policies and Strategies (NPS), led by the Alliance of Bioversity and CIAT, to report, monitor, and analyze what is happening with food in Colombia. It synthesizes and democratizes currently scattered information, assisting in decision-making, legislation on food security, and the coordinated action of various stakeholders.